Al-Akhlāq Aṣ-Ṣadāqah wa Al-Usrah fī Ar-Rusūm Mughāmarāt Manṣūr: Taḥlīl Sīmiyā’ī li Charles Sanders Pierce: Moral Values, Friendship, and Family in The Adventures of Mansour Comics: A Semiotic Analysis of Charles Sanders Peirce - Kholifatunnisa, Aura; Syaifullah; Kholis, Muhammad Nur; Jatmiko, Rumpoko Setyo (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
This study explains the moral representation of friendship and kinship in the animation